2016
DOI: 10.1111/jpy.12415
|View full text |Cite
|
Sign up to set email alerts
|

Classification of phytoplankton cells as live or dead using the vital stains fluorescein diacetate and 5‐chloromethylfluorescein diacetate

Abstract: Regulations for ballast water treatment specify limits on the concentrations of living cells in discharge water. The vital stains fluorescein diacetate (FDA) and 5‐chloromethylfluorescein diacetate (CMFDA) in combination have been recommended for use in verification of ballast water treatment technology. We tested the effectiveness of FDA and CMFDA, singly and in combination, in discriminating between living and heat‐killed populations of 24 species of phytoplankton from seven divisions, verifying with quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…For four of the species, dead cells stained more strongly than living cells. Contrary to indications that a particular taxonomic group, dinoflagellates, was more prone to misclassification using stains (Steinberg et al, 2011;United States, 2016c), the study of 24 taxonomically diverse species in culture showed no relationship between staining patterns and taxonomy (MacIntyre & Cullen, 2016).…”
Section: Validation Of the Accuracy Of Fda+cmfda As Vital Stainsmentioning
confidence: 69%
See 3 more Smart Citations
“…For four of the species, dead cells stained more strongly than living cells. Contrary to indications that a particular taxonomic group, dinoflagellates, was more prone to misclassification using stains (Steinberg et al, 2011;United States, 2016c), the study of 24 taxonomically diverse species in culture showed no relationship between staining patterns and taxonomy (MacIntyre & Cullen, 2016).…”
Section: Validation Of the Accuracy Of Fda+cmfda As Vital Stainsmentioning
confidence: 69%
“…Consistent with recommendations for validating the base assumptions of the FDA+CMFDA method (Drake et al, 2016;United States, 2016c), the basis of the SDC-MPN method was validated using actively growing and heat-killed cultures (MacIntyre & Cullen, 2016). All five of the species tested were accurately classified using SDC-MPN ( Figure 1) whereas fewer than half of 24 species tested with vital stains were accurately classified using FDA+CMFDA.…”
Section: Validation Of the Sdc-mpn Base Methodsmentioning
confidence: 76%
See 2 more Smart Citations
“…fluorescein diacetate (FDA), 5-chloromethylfluorescein diacetate (CMFDA)), or that it is dead (e.g. SYTOX TM Green Dead Cell Stain) (Selvin et al 1988;Veldhuis et al 1997;Reavie et al 2010;MacIntyre et al 2016). Unfortunately, stains such as FDA that result in green intracellular fluorescence in living cells may not be absolute vitality indicators.…”
Section: Introductionmentioning
confidence: 99%